Self-assisted membrane-penetrating helical polypeptides mediate anti-inflammatory RNAi against myocardial ischemic reperfusion (IR) injury. (12th June 2019) - Liang, Qiujun; Li, Fangfang; Li, Yongjuan; Liu, Yong; Lan, Min; Wu, Songhua; Wu, Xuejie; Ji, Yong; Zhang, Rujing; Yin, Lichen
Abstract : Aromatically-modified helical polypeptide mediates membrane-penetrating RAGE siRNA delivery toward anti-inflammatory treatment against myocardial IR injury. Abstract : Anti-inflammatory RNA interference (RNAi) provides a promising paradigm for the treatment of myocardial ischemia reperfusion (IR) injury. To overcome the membrane barriers against intracardial siRNA delivery, various guanidinated helical polypeptides with potent and aromaticity-assisted membrane activities were herein developed and used for the delivery of siRNA against RAGE (siRAGE), a critical regulator of the pro-inflammatory cascade. Aromatic modification of the polypeptide led to notably enhanced trans-membrane siRNA delivery efficiencies, and more importantly, allowed more siRNA cargoes to get internalized via non-endocytosis, an effective pathway toward gene transfection. Subsequently, benzyl-modified polypeptide (P-Ben) was identified as the top-performing material with the highest RAGE silencing efficiency yet lowest cytotoxicity in H9C2 cells. Intracardial injection of the P-Ben/siRAGE polyplexes at 150 μg siRNA per kg led to remarkable RAGE knockdown by ∼85%, thereby attenuating the inflammatory cytokine release and reducing the cardiomyocyte apoptosis as well as myocardium fibrosis to recover the cardiac function after IR injury. This study therefore provides an effective strategy for the design of membrane-penetrating gene delivery materials, and may provide a promising addition to the anti-inflammatory treatment of myocardial IR injury.